Mengurangi Tingkat Plagiarisme melalui Metode Repetitive dalam Penyusunan Proposal Penelitian Tindakan Kelas Mahasiswa PAI FTIK IAIN Pontianak - Andina Nurul Wahidah (Departement of Mathematics Education, 2022)
The rampant plagiarism that occurs, especially in the preparation of scientific work in Higher Education, is a common problem that must be addressed immediately. This research tries to overcome this problem starting with the preparation of student scientific work during lectures, namely Classroom Action Research (CAR) proposals which are the output of CAR courses at PAI Study Program FTIK IAIN Pontianak in 2022. A quantitative approach is used to process research data using descriptive statistical analysis techniques based on the results of the study documents totaling 63 proposals from research subjects in PTK-A and PTK-B classes. Documents were analyzed using Turnitin software, and 3 (three) conclusions were obtained. First, there was a reduction in the level of plagiarism using the repetitive method based on the results of the similiarity index as follows, (a) PTK-A class showed the average similiarity index results in stage I (42.70%), stage II (30.73%) and stage III ( 17.88%), (b) PTK-B class stage I (69.10%), stage II (30.53%) and stage III (23.07%). Second, the repetitive method is carried out in a measurable and planned manner through the three stages starting from planning, implementation and closing. Third, the results of the grading report analysis show that search sources in student documents that are entangled in plagiarism are mostly internet sources (57.29%), student papers (23.59%) and publications (19.12%)